Insect and Mite Management Suggestions for Commercial, Field-grown Statice Production - James F. Price; Curtis Nagle; Elzie McCord, Jr. (EDIS)
Revised! ENY-310, a 30-page fact sheet by James F. Price, Curtis Nagle, and Elzie McCord, Jr., provides a guide to facilitate selection of pesticides for field production of this winter flower crop in Florida. Published by the UF Department of Entomology and Nematology, December 2008.